If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(x-4)=12-3x
We simplify the equation to the form, which is simple to understand
-3(x-4)=12-3x
Reorder the terms in parentheses
+(-3x+12)=12-3x
Remove unnecessary parentheses
-3x+12=+12-3x
We move all terms containing x to the left and all other terms to the right.
-3x+3x=+12-12
We simplify left and right side of the equation.
0x=0
0=0
This equation is an identity, so all real numbers are solutions.
| 42-12t=30 | | 2x-5x=5-9 | | (2x/3)-(4x/5) | | (x+4)2=(4-x)(4+x) | | 2x/3-4x/5 | | 8(x+1)=8x+1 | | 11-3k=-4(1+2k) | | xa=d | | 56=-1+3x | | 7(2a-8)+6=-92 | | 5-9a-14/3(2a) | | Z=-5z | | 2x^3-4x^2= | | 2l+6=6-10 | | Y-2+3x=6+5x | | 1/2x-y=3 | | 4x-(2x-10)=2x-6 | | sqrtx+2=3 | | 12x+10=14x | | -5(3-q)+4=5q | | 5(b+1)-6=2b-16 | | 8.364km= | | 1/3=4/6q | | 2y+3(0)y=10-0 | | 6m-2=-2-7m-m | | 15(x-3)=105 | | 3/4-3/4=0 | | -8(-2b+2)=-128 | | -8(1-4p)=120 | | 6t+3(5+-4)=12(2+-5) | | 6+2(33-x)-3+x= | | (25x)/45=-67 |